Digesting FOREXS: Information Transmission Across Asset Classes and Return Predictability - Bae, Joon Woo; Da, Zhi; Zurita, Virgilio (Management Science, 2024)
We provide novel evidence that equity investors react to currency shocks with a delay. Using the cross-section of currency returns and the relative presence of U.S. firms in foreign economies, we compute a foreign operations-related exchange shock (FOREXS) measure. We find FOREXS to predict firms’ future cash flows and stock returns, driving much of the previously documented underreaction to foreign information. An FOREXS-based long-short strategy yields a 6.74% annualized abnormal return. FOREXS predictive power comes from firms’ incomplete hedging and investors’ limited attention, highlighting the challenges involved when processing information from a different asset class. This paper was accepted by David Sraer, finance. Funding: Z. Da acknowledges financial support from the Beijing Outstanding Young Scientist Program [Grant BJJWZYJH01201910034034] and the 111 Project [Grant B20094]. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2023.4778 .